Synthesis and Properties of Starch Modified Phenol Formaldehyde Resin for Plywood Composites - Yadav, Ranjana (Indian Forester, 2015)
The aim of this work was to develop a Modified Phenol-formaldehyde (PF) resin by partially replacing phenol with starch. Starch-phenol-formaldehyde (SPF) resins were produced by substituting phenol with starch in various percentages. Phenol was replaced by various percentages of starch to keep the phenolic to formalin weight ratio constant to 1:1.6. In the present study 10%, 20% and 30% replacement of phenol by starch were adopted in making SPF. The plywood panels of 4 mm thick, 30cm Ã— 30cm were made and the panels were subjected to test for BWP grade as per IS: 848-2006, Specification of synthetic resin and adhesive for plywood (phenolic and amino plastic resin). The results indicated that the starch was a feasible replacement for up to 30% of the phenol in PF resins for poplar and silver oak species.